2005
DOI: 10.1080/10495390500276882
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Tissue Expression of Chicken Heart Fatty Acid-Binding Protein and Intestine Fatty Acid-Binding Protein Genes

Abstract: Fatty acid-binding proteins (FABPs) are members of a superfamily of lipid-binding proteins, occurring intracellularly in invertebrates and vertebrates. This study was designed to clone and characterize the genes of heart fatty acid-binding protein and intestine fatty acid-binding protein in the chicken. PCR primers were designed according to the chicken EST sequences to amplify cDNA of H-FABP and I-FABP genes from chicken heart and intestinal tissues. Analysis of sequence showed that the cDNA of the chicken H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Fatty‐acid binding proteins (FABP) are found in the animal intestines, liver, heart, skeletal muscle and other tissues. These proteins are involved in fatty‐acid metabolism, including absorption, transportation and regulation of the concentration gradient across cellular membranes (Wang et al , 2005). Intestinal FABP (FABP2) affects animal growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty‐acid binding proteins (FABP) are found in the animal intestines, liver, heart, skeletal muscle and other tissues. These proteins are involved in fatty‐acid metabolism, including absorption, transportation and regulation of the concentration gradient across cellular membranes (Wang et al , 2005). Intestinal FABP (FABP2) affects animal growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…The low molecular weight protein is predominantly detectable in myocardial cytoplasm and lung tissue. It participates in the uptake and transport of long chain fatty acids and is suggested as a promising biomarker of cardiac impairment [98][99][100] . Recent studies indicate, that hFABP can independently predict 28-d mortality and organ failure in patients with sepsis, severe sepsis or septic shock.…”
Section: Heart Type Fatty Acid Binding Proteinmentioning
confidence: 99%
“…These results are consistent with the findings of the present study. However, Wang et al (2005) found that the FABP2 gene was expressed only in intestinal tissues in chickens. The same expression profile was observed in goat (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%